2014
DOI: 10.1371/journal.pone.0094911
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selection Footprints on the X Chromosome in Pig

Abstract: Identifying footprints of selection can provide a straightforward insight into the mechanism of artificial selection and further dig out the causal genes related to important traits. In this study, three between-population and two within-population approaches, the Cross Population Extend Haplotype Homozygosity Test (XPEHH), the Cross Population Composite Likelihood Ratio (XPCLR), the F-statistics (Fst), the Integrated Haplotype Score (iHS) and the Tajima's D, were implemented to detect the selection footprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
1
30
1
1
Order By: Relevance
“…Earlier XWAS in humans revealed candidate functional genes associated with height and fasting insulin (Tukiainen et al 2014). In addition, a previous study in swine using the Illumina Porcine 60K SNP chip showed that genes located in potential selective regions on the X chromosome have a significant effect on meat quality, reproduction and the immune system (Ma et al 2014). In sheep, several genes on the X chromosome are involved in fat deposition, reproduction, the immune system and disease-and biosynthesisrelated pathways (Zhang et al 2013;Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier XWAS in humans revealed candidate functional genes associated with height and fasting insulin (Tukiainen et al 2014). In addition, a previous study in swine using the Illumina Porcine 60K SNP chip showed that genes located in potential selective regions on the X chromosome have a significant effect on meat quality, reproduction and the immune system (Ma et al 2014). In sheep, several genes on the X chromosome are involved in fat deposition, reproduction, the immune system and disease-and biosynthesisrelated pathways (Zhang et al 2013;Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other population genetic measures like Tajima’s D, Fu and Li’s D*, and Fu and Li’s F* suggest the signature of balancing selection in FTO on a significant level. Detection of balancing selection might be explained by the fact that whereas Tajima’s D considers the sites themselves in terms of allele frequencies, it does not take into account the surrounding regions of sites through addressing LD (such as iHS) [ 49 , 50 ]. This is interesting when considering that polymorphisms in the third intron showed the strongest association with BMI in the Sorbs from Germany [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relative extended haplotype homozygosity (REHH) test overcomes limitations of the heterogeneous recombination among chromosomal regions, which may potentially cause some false positives in EHH detection (Qanbari et al 2010). Many recent studies focused on genome-wide selective signature detection were conducted in various pig breeds, including Chinese indigenous breeds and western commercial breeds (Ai et al 2013(Ai et al , 2014Wilkinson et al 2013;Ma et al 2014Ma et al , 2015Wang et al 2014;Yang et al 2014;Moon et al 2015). Wilkinson et al (2013) reported several genes associated with reproduction, growth, and fat deposition traits in European breeds using F ST tests.…”
Section: Introductionmentioning
confidence: 99%